Solar Tides in the Middle and Upper Atmosphere of Mars. Issue 9 (12th September 2020) - Forbes, Jeffrey M.; Zhang, Xiaoli; Forget, Francois; Millour, Ehouarn; Kleinböhl, Armin
Abstract: Solar tides are responsible for much of the spatial‐temporal variability of Mars' upper atmosphere (100–∼200 km). However, the tidal spectrum, its latitude versus Ls variability, and its vertical evolution remain uncertain. In this paper, Mars Climate Sounder temperature measurements at 76 km above Mars' areoid are used to construct a multiyear latitude versus Ls climatology of the tidal spectrum. The most important spectral components include the solar‐synchronous ("migrating") components DW1, SW2, and the solar‐asynchronous ("nonmigrating") tides DE3, DE2, DE1, SE1, S0, and SW1. The Mars Climate Database (MCD), which provides predictions from the Laboratoire de Météorologie Dynamique Global Climate Model, captures particularly well the amplitudes and key structural features of the solar‐asynchronous tides at 76 km that furthermore underly the large longitudinal structures in density that are observed between 100 and 200 km. Height‐latitude and latitude‐Ls structures of MCD density perturbations are therefore examined between 76 and 172 km and interpreted in terms of mean wind and dissipation effects. In particular, due to the smaller radius and more intense zonal‐mean zonal winds at Mars compared to Earth, Doppler‐shift effects are significantly exaggerated compared to Earth. Evidence is also provided for nonnegligible contributions to density variability from stationary planetary waves which arise from tide‐tide nonlinear interactions. It is moreover shown that MCD captures the salient amplitude and phase characteristics of the ∼±30–60% longitudinal density perturbations measured by the Mars Global Surveyor accelerometer. This, and the excellent MCD‐MCS agreement at 76 km, lends credibility to the ability of MCD to provide new insights into thermosphere density variability at Mars due to vertical coupling by solar tides. Key Points: Multiyear latitude vs. Ls structures of 76 km DW1, SW2, DE3, DE2, DE1, SE1, S0, and SW1 tidal temperatures derived from MRO/MCS measurements Mars MCD tidal spectrum at 76 km compares well in amplitude and structure with MCS climatology MCD latitude‐height tidal structures influenced by mean winds and dissipation provide insights into density variability at >100 km altitude